Kajian Sosio-Historis tentang Pandangan Dunia Atoni Pah Meto dalam Ritus Poitan Liana - Afi, Kristian E.Y.M; Banamtuan, Maglon F (UI Scholars Hub, 2020)
This article describes the world view of the people of South Central Timor Regency regarding Atoni Pah Meto in the Poitan Liana Rite. With qualitative descriptive methods, the paper formulated (1) Poitan Liana Rite means the kinship displayed in the role of Atoin Amaf in belief in Uis Neno, Uis Pah, and the ancestors through symbolic actions and speech; (2) Timorese view their life as an integral part of supernatural life, and the continuation of people’s lives in harmony between social order and cosmic order. Uis Neno, Uis Pah, and Ancestors are believed to be a supernatural power involved in human life. All forms of supernatural power interventions are in the context of the life of Atoni Pah Meto that proceeds to actualize themselves as “Responsible on earth”. (3) All human efforts are seen as a blessing from Uis Neno, Uis Pah, and the ancestors. Overall Poitan Liana’s ceremony contains meaning related to the understanding of self, nature, and society on one hand, as well as relations with supernatural powers on the other. In this vertical and horizontal dimension, Orang Boti directs himself to the vertical dimension to maintain his life in the horizontal dimension.